The Effect of Roasting Methods of Ingredients The Songgak Tribe Sasak Herbal on Active Compounds Using Gas Chromatography Mas Spectroscopy (Gc-Ms) Analysis) - Agrijanti, Agrijanti; Kusuma Dewi, Lale Budi; Khusuma, Ari; Wardoyo, Eustachius Hagni (Jurnal Kesehatan Prima, 2024)
Songgak is a concoction of the Sasak tribe of Lombok in West Nusa Tenggara. It consists of coffee mixed with groundwood, cloves, black pepper, coriander, and nutmeg. The original recipe involves roasting the spices before mixing them with coffee, namely using a frying pan over a stove. The roasting process is carried out without controlling the temperature and roasting time, so the roasted ingredients need to be standardized(Dewi et  al., 2021). GCMS is a tool used to analyze compounds in samples using chemical separation methods, mainly chromatography. The compounds in the mixture are separated in a chromatographic column. The separation mechanism between several compounds occurs due to differences in the solubility values of each in the moving solvent and differences in the absorption of each of the competing compounds into the stationary phase (Gross, 2017). In this research, variations will be carried out on spices, namely T1 original treatment of roasting spices over fire for 8 minutes, T2 drying spices in sunlight, T3 oven for 5 minutes, T5 oven for 5 minutes, T4 oven for 15 minutes and T5 oven for 15 minutes. In the T4 treatment, namely oven for 10 minutes, the results of the analysis of the substance content with the most types, namely 20 types, were obtained. The active anti-microbial compound found in all treatments was Hexadecanoic acid, 2-hydroxy-1-(h)(C19 H38 O4) BM:330, which helps inhibit the growth of cancer cells. (National Library Medicine, n.d.). Octadecanoic acid (CAS) Stear (C18 H34 O2) BM:282 Anti-inflammatory, Antiandrogenic Cancer prevention, Hypocholesterolemia Dermatigenic, 5-Alpha reductase inhibitor, Anemiagenic, Insecticide (Natarajan et al., 2019) and Tetradecanoic acid (CAS) Myris (C14 H28 O2) BM:228 as anti-inflammatory and anti-nociceptive.